Early Language, Literacy, and Numeracy (ELLN) Program in Schools: Experiences of Grade Three Teachers - Anagon, Cherry Joie A. (International Journal of Research in Interdisciplinary Studies, 2024)
This phenomenological inquiry explored the experiences of teachers in implementing the ELLN program at Sto. Tomas West District, Division of Davao del Norte. In exploring the experiences of the ten participants, I employed the qualitative – phenomenological study of which primary instrument of data gathering was through in- depth interview. Results revealed that the themes emerged on the experiences in implementing the ELLN program, they shared three major themes namely, pedagogical challenges and adaptations, assessment and accountability, and parent and community involvement. Additionally, the major themes on the coping mechanisms of teachers in implementing the ELLN program in the school were professional development and support, work-life balance, and student-centered approaches. Finally, on the participants’ insights in implementing the Early Language, Literacy, and Numeracy (ELLN) program, the following were the emergent themes namely, student progress and growth, adaptability and continuous learning, and holistic development. The implementation of the Early Language, Literacy, and Numeracy (ELLN) Program as experienced by teachers holds several research implications that can guide future investigations and improvements in educational practice. Research can delve deeper into assessing the program's effectiveness in enhancing student language, literacy, and numeracy skills. Long-term studies that track student outcomes and academic performance can provide insights into the program's impact on a broader scale, informing curriculum development and educational policies. In addition, exploring the specific professional development needs of teachers in the context of the ELLN program is essential. Research can focus on the effectiveness of various training methods, workshops, and ongoing support systems to enhance teacher competence and adaptability in implementing the program.